Draft Sixth Five Year Plan 1980-85 and Annual Plan 1981-82 Vol. I Government of Manipur - Planning Commission (Planning Commission, 1980)
The State of Manipur literally meaning the "Land of Jewels" consisting of a valley of about 2230 sq. kms. in area situated at a height of 790 metres surrounded by a hilly tract which is about nine times the area of the valley i.e. 20,126 sq. kms., is a completely land locked State situated in the north eastern region of the Country. It borders with Burma over a stretch of 352 kms. in the east, Nagaland in the north, Assam in the west and Mizoram in the south. Rows and rows of rolling hills cover 90% of the area of this State surrounding the heart land—the valley in the centre and forming a preventive barrier that isolates Manipur from the neighbouring sister States and Union Territories of the Country.
State of Planning Department, Government of Manipur